Growth And Survival Rate of Tilapia (Oreochromis niloticus) Fed With Different Level of Azolla microphylla - Wahdania, Wahdania; Saharuddin, Saharuddin; Yuniati, Dewi (Journal of Aquaculture Development and Environment, 2024)
Azolla microphylla is abundant in nature and has not been utilized optimally. A. microphylla can grow and bloom quickly. The protein content of A. microphylla is quite high, 19.54%-28.12% . Furthermore A. microphylla also has 7-10% amino acids, especially 0.24% lysine. Utilization of A. microphylla as feed potential for aquaculture. This research aims to determine the effect and optimum dose of combination A. microphylla flour with artificial feed on growth and survival rate of tilapia (O. niloticus). This study used a Completely Randomized Design with 4 (four) treatments and 3 (three) replications, repectively treatment A (0% A. microphylla), treatment B (10% A. microphylla), treatment C (A. microphylla 15%), and treatment D (A microphylla 20%). The parameters tested were specific growth rate (SGR), growth rate (GR), survival rate (SR) and feed conversion ratio (FCR). The tilapia used had an average initial body weight of 1.10 g with a stocking density of 10 fishes/containers. The fish reared for 30 days and fed 2 times a day. The result showed that there was no significant difference in specific growth rate, growth rate, survival rate and FCR (P0.05). A. microphylla can be used as a combination of artificial feed up to 20%, it showed the same growth and survival rate as the control treatment.